2003
DOI: 10.1002/dev.10140
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic and stochastic processes in children's isometric force variability

Abstract: This study examined the influence of deterministic and stochastic processes (including white Gaussian noise) on reductions in the amount of force output variability through childhood. The structure of the force signal produced during a constant isometric pinch grip task was examined as a function of age (6, 8, and 10 years, and young adults), availability of feedback information (with and without vision), digit (thumb and index finger), and force level (5, 15, 25, and 35% of maximal voluntary contraction). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…DFA analysis demonstrated that without visual feedback the DFA exponent was greater than that with visual feedback for both the CTS and control groups, suggesting that absence of visual feedback reduced the structural variability of pinch forces (Athreya et al, 2012; Li et al, 2013a). This finding corroborates previous studies demonstrating that visual feedback altered the time-dependent properties of force variability during a sustained contraction by a single digit (Athreya et al, 2012; Hong and Newell, 2008; Sosnoff and Newell, 2005) or during pinch with the thumb and index finger (Deutsch and Newell, 2002, 2003; Li et al, 2013a; Vaillancourt et al, 2001). Higher irregularity of pinch force under the visual condition is probably attributed to visual-guided force correction; whereas the central nervous system exerts a less fluctuated muscle contraction in the absence of this visuomotor correction (Athreya et al, 2012; Baweja et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…DFA analysis demonstrated that without visual feedback the DFA exponent was greater than that with visual feedback for both the CTS and control groups, suggesting that absence of visual feedback reduced the structural variability of pinch forces (Athreya et al, 2012; Li et al, 2013a). This finding corroborates previous studies demonstrating that visual feedback altered the time-dependent properties of force variability during a sustained contraction by a single digit (Athreya et al, 2012; Hong and Newell, 2008; Sosnoff and Newell, 2005) or during pinch with the thumb and index finger (Deutsch and Newell, 2002, 2003; Li et al, 2013a; Vaillancourt et al, 2001). Higher irregularity of pinch force under the visual condition is probably attributed to visual-guided force correction; whereas the central nervous system exerts a less fluctuated muscle contraction in the absence of this visuomotor correction (Athreya et al, 2012; Baweja et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…This indicates consistent agerelated improvements of TD children's isometric control of finger force/torque in all tasks. Similar findings have been reported in previous studies with finger pressing tasks [7;18;27] and pinching tasks [8][9][10].…”
supporting
confidence: 91%
“…This interval encompasses the steady-state portion wherein participants must integrate real-time visual feedback to continuously maintain isometric force. Continuous motor tasks rely on sensory feedback mechanisms to a greater degree than discrete motor tasks, such that individuals can continuously adjust their motor output to stay on target (Deutsch and Newell 2001; Deutsch and Newell 2003). In a previous study using a similar hand-grip task, 30 seconds of visually guided force production was associated with brain activity in right-lateralized regions including dorsolateral prefrontal cortex, ventral premotor cortex, and inferior parietal lobe (IPL) (Neely et al 2013a).…”
Section: Discussionmentioning
confidence: 99%